Facilitation of learner autonomy in EFL: Teacher's and students’ perspectives of the 'Work in Progress' textbook - Berlin, Astri Winandari; Wirza, Yanty (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study investigates how the ‘Work in Progress’ English textbook facilitates learner autonomy, as perceived by an English teacher and tenth-grade students. A qualitative case study approach was used, with data collected through semi-structured interviews with one teacher and ten students who use the textbook as their main learning material. Thematic analysis was applied to categorize findings according to the levels of learner autonomy: Awareness, Involvement, Intervention, Creation, and Transcendence. The results show that the textbook mainly supports autonomy at the Awareness, Involvement, Intervention, and Transcendence levels, but lack support in Creation level. It helps students understand learning goals, provides choices, allows some flexibility in adapting tasks, and connects classroom materials to real-life contexts. However, opportunity for students to set their own learning goals and design their own tasks is limited, with such experience coming from teacher-initiated activities rather than the textbook itself. Both the teacher and students viewed the textbook positively for its clear structure and flexibility but noted the need for more support, such as professional development for teachers and scaffolding for students, to better develop learner autonomy. Many students still relied on external tools like translation apps, showing ongoing challenges in independent learning. This study highlights the important role of textbooks in supporting various levels of learner autonomy in EFL classrooms, emphasizing the need for materials that not only provide clear instructions but also promote learners’ ability to manage their own learning. It also underscores the significance of teacher professional development to equip educators with the skills necessary to foster autonomy effectively. These findings have practical implications for curriculum developers, textbook authors, and educational policymakers aiming to enhance learner-centered practices and promote learner independence in language education.